Equalização Autodidata: Fundamentos, Novas Propostas e Perspectivas DOI: 10.14209/jcis.1995.3 - A. F. da Rocha, C.; M. T. Romano, J. (Journal of Communication and Information Systems, 2015)
Self-learning equalization is a technique for communication channel equalization without the aid of the usual training sequence. This paper provides an overview about three self-learning approaches: the Bussgang Techniques, the High order Statistics (HOS) Techniques and the Predictive Techniques. The latter are based on the linear prediction theory that we have proposed in previous publications. Simulations results compare the performance of the different approaches. These results show the potentiality of the predictive techniques.